The Magnitude of Regional‐Scale Tree Mortality Caused by the Invasive Pathogen Phytophthora ramorum. Issue 7 (17th July 2020) - Cobb, Richard C.; Haas, Sarah E.; Kruskamp, Nicholas; Dillon, Whalen W.; Swiecki, Tedmund J.; Rizzo, David M.; Frankel, Susan J.; Meentemeyer, Ross K.
Abstract: Forest pathogens are important drivers of tree mortality across the globe, but it is exceptionally challenging to gather and build unbiased quantitative models of their impacts. Here we harness the rare data set matching the spatial scale of pathogen invasion, host, and disease heterogeneity to estimate infection and mortality for the four most susceptible host species of Phytophthora ramorum, an invasive pathogen that drives the most important biological cause of tree mortality in a broad geographic region of coastal California and southwest Oregon. As of 2012, the most current field survey year, we estimate 17.5 (±4.6, 95% CI [confidence interval]) million tanoak ( Notholithocarpus densiflorus ) stems were pathogen killed with an additional 71 (±21.5) million infected. We estimated 9.0 million (±2.2) coast live oak ( Quercus agrifolia ) and 1.7 million (±0.5) California black oak ( Quercus kelloggii ) stems are disease impacted (mortality and infection combined). Lastly, our estimates suggest infection in 95.2 million (±8.6) California bay laurel ( Umbellularia californica ), which does not suffer mortality from infection and represents a critical source of continued spread. Prevalent infection as of 2012 suggests the cumulative number of disease‐killed stems likely increased from 20.8 to 42.8 million between 2012 and 2019 for all species. While these impacts are substantial, most host populations occur in a yet to be invaded region of northern California indicating that the disease will intensify in the coming decades. Key Points: Large‐scale tree mortality events are difficult to quantify even though they influence landscape and atmospheric processes of great societal value The pathogen Phytophthora ramorum has killed at least 48 million stems and infected about 150 million more since 1995, while about 1.8 billion remain at risk Although challenging, region‐scale tree mortality can be quantified with empirical data and scalable models that match extent of the event